Why are there no low-δ18O magmas In convergent margins? A case of the Central Andes, Northern Chile - Sigauke, Connie (Department of Geological Sciences, 2022)
It has long been thought that low-δ 18O magmas (<5.7‰) are only found in extensional tectonic settings. Low-δ 18O magmas are rare, worldwide, especially in subduction zone settings. The main objective of this study was to conduct a search for low-δ 18O magmas in the Central Volcanic Zone (CVZ) of the Andes, to verify if their rarity is due to under sampling. If no low-δ18O magmas were found, the question of why low-δ 18O magmas have appeared to be absent from the region would be addressed. This study has determined the variation in oxygen isotope composition of rocks across the CVZ, ranging in age from about 12 Ma to Recent. The δ18O values were measured in selected bulk rock samples and separated quartz phenocrysts in order to identify potential low-δ 18O rocks (from whole rock analyses) and magmas (from the quartz phenocrysts). The average δ18O values for quartz phenocrysts and whole rocks are 8.6‰ and 10.5‰ respectively, and no low-δ 18O magmas were found. Hydrogen isotope values range from -32 to -119‰, with the highest value in the most altered rock. The results from this study show no evidence for low-δ 18O magmas; the lowest value (5.0‰) was found in one sample (for both quartz and whole rock) and this sample appears to have been affected by interaction with meteoric water. The overall high δ18O values in the CVZ rocks are best explained as the result of alteration by fluids having high δ18O values. These were probably meteoric fluid whose δ18O were enriched due to fluid-rock exchange. The high δ18O values of the magmas must reflect the absence of low-δ 18O rocks that could be melted, and a relatively crustal input to magmas. This study agrees with the conclusions of Folkes et al. (2013), which explains the absence of low-δ 18O magmas as a result of tectonic history and climatic conditions of the central Andes; where low precipitation and high evaporation rates, high aridity, limited supply of meteoric waters, and high elevation all played significant roles in the lack of low-δ 18O magmas in the region.